2011
DOI: 10.1258/om.2011.110080
|View full text |Cite|
|
Sign up to set email alerts
|

Operative delivery rates following induction of labour for obstetric cholestasis

Abstract: Summary: The aim of this study was to determine whether women induced for obstetric cholestasis (OC) have increased rates of operative delivery compared with women without OC who are induced. This retrospective case-control study included 64 women with OC (singleton pregnancies), who had labour induced compared with two control groups (matched for parity and gestational week at delivery). The majority of women were induced at 37 weeks. We found no significant increase in the rate of operative or assisted deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Another retrospective case-control study of 64 inductions of labour due to ICP revealed no increased risk of vaginal surgical delivery or caesarean section. Other complication rates, e.g., for postpartum haemorrhage, were comparable to the control group of induced labour without ICP 159 .…”
Section: Delivery Managementmentioning
confidence: 62%
See 1 more Smart Citation
“…Another retrospective case-control study of 64 inductions of labour due to ICP revealed no increased risk of vaginal surgical delivery or caesarean section. Other complication rates, e.g., for postpartum haemorrhage, were comparable to the control group of induced labour without ICP 159 .…”
Section: Delivery Managementmentioning
confidence: 62%
“…Die weitere Komplikationsrate z. B. für postpartale Blutung war vergleichbar zur Kontrollgruppe aus Geburtseinleitungen ohne ICP 159 .…”
Section: Entbindungsmodusunclassified
“…Serum bile acid concentrations over 40 µmol/L as high-risk pregnancy with ICP; no difference is observed in modes of delivery of pregnancies that are terminated at the 37th gestational week [20]. In a retrospective study, there was no increase in intervention delivery or cesarean delivery rates in women with ICP [21]. Also, no difference was observed in terms of the first and second stage of the delivery periods of pregnant women with ICP compared with the control group.…”
Section: Discussionmentioning
confidence: 89%
“…Regular check-ins and diagnostic lab tests are a part of maternal monitoring (bile acids, alanine aminotransferase, aspartate aminotransferase, gamma-glutamyl transferase, bilirubin, and prothrombin time). Pregnancy monitoring should primarily use cardiotocography (CTG) and ultrasound screening, with intervals determined by the mother's pre-existing conditions and the total bile acid level [ 16 ].…”
Section: Discussionmentioning
confidence: 99%